Pengaruh Kompetensi dan Beban Kerja terhadap Kinerja Karyawan pada PT MADUSARI MAS Surabaya - Rizal Firmansyah; Dwiarko Nugrohoseno (Jurnal Ilmu Manajemen, 2022)
An organization should change to face a challenge ahead that cannot be avoided. Challenges faced by an organization or company can come from various aspects. Good teamwork is needed, and competencies are supportive so companies can survive because challenges often create competition between companies. This study aimed to determine and analyze the influence of competencies and workload on employee performance at PT Madusari Mas Surabaya. This research is quantitative research with a total sample of 150 employees. The measuring instrument used is an interview, observations, and questionnaires. Data were analyzed by using multiple linear regression analysis techniques with the help of Statistical Package for the Social Sciences software (SPSS 23). The results of this study explain that competency has a significant positive effect on employee performance, while workload does not. Competence and workload simultaneously affect employee performance. Companies must consider the competencies possessed by employees during the recruitment process. In addition, to improve employee performance, companies must consider the workload of employees.